Resource Recovery from Wastewater by Biological Technologies: Opportunities, Challenges, and Prospects - Puyol, Daniel; Batstone, Damien J.; Hülsen, Tim; Astals, Sergi; Peces, Miriam; Krömer, Jens O. (Frontiers in Microbiology, 2017)
Limits in resource availability are driving a change in current societal production systems, changing the focus from residues treatment, such as wastewater treatment, towards resource recovery. Biotechnological processes offer an economic and versatile way to concentrate and transform resources from waste/wastewater into valuable products, which is a prerequisite for the technological development of a cradle-to-cradle bio-based economy. This review identifies emerging technologies that enable resource recovery across the wastewater treatment cycle. As such, bioenergy in the form of biohydrogen (by photo and dark fermentation processes) and biogas (during anaerobic digestion processes) have been classic targets, whereby, direct transformation of lipidic biomass into biodiesel also gained attention. This concept is similar to previous biofuel concepts, but more sustainable, as 3rd generation biofuels and other resources can be produced from waste biomass. The production of high value biopolymers (e.g. for bioplastics manufacturing) from organic acids, hydrogen, and methane is another option for carbon recovery. The recovery of carbon and nutrients can be achieved by organic fertilizer production, or single cell protein generation (depending on the source) which may be utilized as feed, feed additives, next generation fertilizers, or even as probiotics. Additionlly, chemical oxidation-reduction and bioelectrochemical systems can recover inorganics or synthesize organic products beyond the natural microbial metabolism. Anticipating the next generation of wastewater treatment plants driven by biological recovery technologies, this review is focused on the generation and re-synthesis of energetic resources and key resources to be recycled as raw materials in a cradle-to-cradle economy concept.